A macroscale finite element approach for simulating the bending behaviour of biaxial fabrics. (3rd May 2020) - Yu, F.; Chen, S.; Viisainen, J.V.; Sutcliffe, M.P.F.; Harper, L.T.; Warrior, N.A.
Abstract: A macroscale finite element (FE) model was developed to simulate the forming behaviour of biaxial fabrics, incorporating the effects of bending stiffness to predict fabric wrinkling. The dependency of the bending stiffness on the fibre orientation was addressed by extending a non-orthogonal constitutive framework previously developed for biaxial fabric materials. The nonlinear bending behaviour of a biaxial non-crimp fabric (NCF) with pillar stitches was characterised by a revised cantilever test using structured light scanning to measure specimen curvature, providing input data for the material model. Simulations were performed to replicate the bias-extension behaviour of the NCF material, showing good agreement with experimental data. Wrinkles were observed within the central area of the specimen at low extension, which consequently affect the uniformity of the shear angle distribution in the region where pure shear is expected.